ANALISIS IMPLEMENTASI KEBIJAKAN PENDIDIKAN AGAMA ISLAM SEBAGAI PENDIDIKAN UMUM DAN KARAKTER DI PERGURUAN TINGGI (Studi Kasus di Institut Teknologi Bandung dan Universitas Pendidikan Indonesia) - Agus Fakhruddin, - (2021)
The Islamic Religious Education (henceforth IRE) policy in higher education is one of the government's initiatives in building the nation's character. The success of these initiatives is contingent, among other things, on the ability of universities to implement IRE policy as general and character education. To date, the implementation of such a policy has not been optimal as research has shown. The present study generally sought to analyze the implementation of the policy; in particular, it was aimed at describing and analyzing the value and meaning of IRE policy content and its implementation through communication, resources, disposition/attitude of the implementers, and the structure of the university bureaucracy. Through a qualitative approach, this research employed a descriptive case study method in IRE settings at Bandung Institute of Technology and Indonesia University of Education. As a key research instrument, the researcher used observations, interviews, and document studies as data collection techniques. Through data reduction, data display, and data verification, this study discovered that IRE policies in higher education manifest values of religious, nationalism, multiculturalism, logic, meaningfulness, and professionalism in character development and IRE is positioned as general and character education. As part of implementation efforts of the IRE policy, the two universities under study exhibit their own unique, valuable, and meaningful interpretations and strategies through communication use much communication media, modern and qualified resources, personal and institutional dispositions systemically designed, and a tiered bureaucratic structure. However, weaknesses prevail in institutional authority, the use of information technology in teaching, and supervision of students' religious activities outside of lectures. Keywords: values education, personality development, religious education